Formulation development and evaluation of therapeutic contact lens loaded with ganciclovir - Harsolekar, Mohit; Ansari, Mudassir; Supe, Shibani; Singh, Kavita (International ophthalmology, 2023)
Purpose In the present investigation ganciclovir (GAN) loaded microparticles dispersed in hydrogel-based contact lenses were fabricated, characterized and evaluated for eye irritation. Methods GAN-Hydroxy Propyl Methyl Cellulose (HPMC) microparticles were prepared by solvent evaporation method and evaluated for entrapment efficiency, drug content and drug release. The Polyhydroxyethylmethacrylate (pHEMA) contact lenses were synthesized by free radical polymerization reaction using crosslinkers like ethylene glycoldimethacrylate and photoinitiator such as IRGACURE 1173 ® , in UVB light, λ 365 nm. The GAN-HPMC microparticles when incorporated into the premonomer mixture and polymerized together give rise to a particle dispersion system in the hydrogel contact lenses. The contact lenses were studied for surface morphology, transmittance, swelling, drug release, Na + ion permeability and hens egg test chorioallantoic membrane assay (HETCAM). Results Hydrogel contact lens exhibited satisfactory surface morphology, transmittance, swelling, Na + ion permeability (3.72 × 106 mm 2 /min) and a release of 48 h suggesting a potential for prolonged ocular drug delivery. Furthermore, HETCAM exhibited no signs of ocular irritation. Conclusion The developed delivery platform is a promising alternative to conventional dosage forms like eye drops, suspensions and ointments due to its increase in the residence time attributed to its prolonged release profile.